Exogenous carbohydrate oxidation and glucose kinetics during prolonged cycling exercise: effects of gender - Wallis, G. A.; Dawson, R.; Achten, J.; Jeukendrup, A. E. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction Studies using male subjects indicate that ingested carbohydrates can only be oxidised at rates up to ~1 g.min-1 during endurance exercise, and this limitation is related to intestinal or hepatic processes (for review see Jeukendrup and Jentjens, 2000). One study (Riddell et al, 2003) has measured exogenous carbohydrate oxidation in males and females during 90 min cycling exercise and reported similar oxidation rates during the final 60 min of exercise (~0.38-0.39 g.min-1). The purpose of this study was to quantify exogenous carbohydrate oxidation during 120 min cycling exercise with ingestion of large amounts of carbohydrate (1.5 g.min-1) in a group of male and female cyclists. In addition to this, the stable isotope [6,6-2H2]-glucose was administered in order to investigate potential gender differences in glucose kinetics during exercise with carbohydrate ingestion. Methods Eight male and eight female trained cyclists (matched for age, fitness, training history and current training status) completed two exercise trials in a random order. Each trial consisted of 120 min cycling at 55% maximum power output (~68-70% VO2max) while subjects received a solution providing either 1.5 g.min-1 of glucose or plain water. In order to quantify exogenous carbohydrate oxidation, corn-derived glucose was used, which has a high natural abundance of 13C. In addition, a primed continuous infusion of [6,6-2H2]-glucose was administered throughout both trials in order to quantify glucose kinetics (data not available at time of submission). The oxidation rate of the ingested carbohydrate and total endogenous substrates was determined using stable isotope methods and indirect calorimetry Females were tested in the follicular phase of their menstrual cycle. Results Exogenous carbohydrate oxidation rates increased during exercise and reached peak values of 0.82±0.08 and 0.71±0.06 g.min-1 for males and females respectively (ns, Figure 1). Oxidation rates averaged over the last 60 min of exercise did not differ between males and females (0.70±0.05 and 0.63±0.05 g.min-1 for males and females respectively, P=0.43). There was no significant difference between genders in the contribution of fat, endogenous carbohydrate and exogenous carbohydrate oxidation to total energy expenditure during exercise (Figure 2). Discussion/Conclusion The present study confirms that exogenous carbohydrate oxidation is similar during exercise in males and females. This is consistent with the suggestion that intestinal carbohydrate absorption and subsequent entry into the systemic circulation is a major limiting factor for exogenous carbohydrate oxidation when large amounts of carbohydrates are ingested during exercise (Jeukendrup et al, 1999). In addition, the similar contribution of substrates to energy expenditure suggests that male and female athletes respond in an identical manner to carbohydrate feeding during exercise.